The C-terminal fragment of axon guidance molecule Slit3 binds heparin and neutralizes heparin's anticoagulant activity - Condac, Eduard; Giese, Christina; Harenberg, Job (Glycobiology, 2012)
Abstract. Slit3 is a large molecule with multiple domains and belongs to axon guidance families. To date, the biological functions of Slit3 are still largely u
Gesehen am 04.10.2018